Analytical study of adolescent pregnancies at a tertiary care centre - Srivastava, Shubha; Chandra, Madhuri; Singh, Umesh Kumar (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: According to World Health Organization, about 16 million girls aged 15 to 19 and some 1 million girls under the age of 15 give birth every year. Teenage pregnancies have shown association with higher risks of prematurity, low birth weight, preeclampsia and anaemia as compared to adult pregnancies. The present study was analytical study of pregnant adolescent girls and feto-maternal outcome at a tertiary care centre. Methods: Girls between 10 to19 years, who attended the antenatal clinic and/or who were admitted in the hospital while pregnant or during labour were included in the study. A questionnaire along with detailed history and examination were done. Adolescents who were admitted for confinement, details of labour and mode of delivery were noted. The newborn was assessed in context of prematurity, IUGR or any other complications and referral to NICU. Results: Of the 1870 adolescent girls attending the OPD, 1234 (65.98%) were pregnant. There were 429 (4.02%) teenage deliveries in the institute during the study period. The girls were mostly married, older teenagers and primigravidas. The use of contraception was poor and awareness regarding antenatal care was lacking. The most common risk factor was anemia. The other risk factors included HDP, preterm labor, PROM, IUGR, hemorrhage and previous LSCS. Conclusions: Early childbearing increases the risks for both mothers and their newborns. A delay in marriage givesadolescents opportunities for higher education, thus empowers them. Sex education should be a part of the school curriculum. Good antenatal care may reduce complications of teenage pregnancy.